eLaunceston Revisited – A Novel Regional Research Project from 1999 - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2021)
An historical paper from 1999 is republished because of its relevance to using digital communications to boost regional communities and their digital economies. Telstra Research Laboratories created a community website for Launceston Tasmania, with local stakeholder oversight, to test whether locally oriented information can increase the value of the Internet to existing users and make digital access more attractive to non-users.